Aplikasi Label Pintar Edible dari Ekstrak Antosianin Ubi Jalar Ungu (Ipamoea Batatas L.) untuk Monitoring Kesegaran Sayuran Cabai Hijau (Capsicum Annuum L.) - Aissa Dinar Yanuariski; Bambang Kuswandi; Ari Satia Nugraha (Pustaka Kesehatan, 2020)
Vegetable products are foods that are popular with many people. One vegetable product such as green chili is a vegetable commodity that cannot be abandoned by society in daily life. This was followed by demands for quality of green chili products. so that an analytical tool is needed that can analyze the freshness of green chili easily and practically. This study aims to develop an edible freshness sensor based on anthocyanin indicators from purple sweet potato extract (Ipomoea batatas L.) with a membrane mixture of cassava starch and chitosan. The edible freshness sensor can be applied as a freshness sensor and know the freshness level of green chili with various parameters. Tests for green chili freshness test included pH test, weight loss, texture value, and sensory evaluation test. The color change of the edible freshness sensor was observed visually and tested using the ImageJ program to determine the mean green value. The results show the color change of the freshness sensor is dark purple when the green chili is fresh, the light purple is still fresh and the light green is no longer fresh or rotten. The mean value of the green sensor for edible freshness increased along with the decline in the quality of green chili in the packaging. Keywords: Anthocyanin, tapioca starch, chitosan, green chilli